Labyrinthine patterns transitions - S. Echeverría-Alar; M. G. Clerc (Physical Review Research, 2020)
Macroscopic systems with injection and dissipation of energy exhibit intricate dissipative structures. Labyrinthine patterns are disordered spatial structures arising into homogeneous media that show a short-range order. Here, we investigate the stability properties, classification, and transitions of labyrinthine patterns. Based on a prototype pattern forming model, we characterize the existence of three types of labyrinthine patterns—fingerprint type, glassy, and scurfy—and reveal the bifurcation diagram. The defects density, free energy, structure factor, and correlation length are used as order parameters.